Arteriovenous malformation of face - Ashok Kumar; Meenu Mittal; Dhirendra Srivastava; Vipul Jaetli; Sunil Chaudhary (Wolters Kluwer Medknow Publications, 2017)
Arteriovenous malformations (AVMs) are rare congenital vascular malformations accounting only 1.5% of all vascular anomalies with 50% occurrence in the oral and maxillofacial region. It usually results from birth defects of the vasculature. A literature search revealed only few case reports of AVMs in the facial region. Lack of meticulous diagnosis, scarcity of knowledge, and paucity of literature can result in their exsanguinations leading to fatal hemorrhagic incidents after various dental procedures such as tooth extraction, surgical intervention, puncture wound, or blunt injury in involved area. The present case describes the accidental diagnosis of asymptomatic high-flow AVMs in the facial region of pediatric patient reported primarily for the treatment of periapical abscess. This case report is unique because although there was no history of bleeding episodes, thorough examination and investigations diagnosed it as high-flow vascular malformation. It is important for the dental practitioner to be aware of AVM which may be present in the head and neck region that can produce fatal bleeding episodes during various dental procedures. Proper diagnosis of AVMs through complete history, precise clinical examination, and advanced imaging modalities can help in preventing serious life-threatening complications.